The Influence of Organizational Commitment, Work Discipline, and Workload on Employee Performance with Job Satisfaction as an Intervening Variable - yudha, yudha mahendra; Prabowo, Heri; Putri, Noventia Karina (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
In this era of globalization, the problem of human resources has become one of the problems that affects the resilience of a company. The importance of managing human resources is caused by humans themselves who are the main actors in operational activities aimed at achieving the success of a company's goals. Researchers use quantitative research to analyze data descriptively using descriptive analysis methods. The respondents of this research were all employees of PT. Pos Indonesia Semarang as many as 92 people. The method used by researchers in selecting samples in this research is nonprobability sampling with a saturated sampling category. This data analysis technique uses Smart Pls in processing data. The results of this research show that the Organizational Commitment variable has a significant effect on employee performance. Work Discipline has a significant effect on Employee Performance. Workload has a significant effect on employee performance. Job Satisfaction has no effect on Employee Performance. Organizational Commitment has a significant effect on Job Satisfaction. Work Discipline has no effect on Job Satisfaction. Workload has a significant effect on Job Satisfaction. Organizational Commitment influences Employee Performance, through Job Satisfaction as an intervening variable. Work Discipline has no effect on Employee Performance, through Job Satisfaction as an intervening variable. Workload influences employee performance, through job satisfaction as an intervening variable. Keywords: Organizational commitment, Work discipline, Workload, Employee performance, Job satisfaction